Clinical Phenotype of Respiratory Syncytial Virus Bronchiolitis before and during the Coronavirus Disease 2019 Pandemic - Rodríguez-Fernández, Rosa; González-Martínez, Felipe; Perez-Moreno, Jimena; González-Sánchez, María Isabel; de la Mata Navazo, Sara; Toledo del Castillo, Blanca; Saavedra Lozano, Jesus; Voltas Espinosa, Lucia; Manso Perez, Sara; Miñarro Berlanga, María; Mejias, Asuncion; Ramilo, Octavio (American Journal of Perinatology, 2022)
Objective The main objective of this report was to comprehensively analyze the clinical characteristics of children hospitalized with respiratory syncytial virus (RSV) infections in 2021 during the coronavirus disease 2019 (COVID-19) pandemic and to compare them with those in the five previous RSV seasons. We hypothesized that the clinical and demographic features of children hospitalized with RSV infection in 2021 were different from those hospitalized in previous respiratory seasons.Study Design In this retrospective observational study, children younger than 2 years hospitalized with RSV bronchiolitis from January 1, 2015, to December 31, 2021, at the Department of Pediatrics of the Hospital Gregorio Marañón, Madrid, Spain, were included. We compared the clinical characteristics of children hospitalized with RSV bronchiolitis in the five seasons before the COVID-19 pandemic and during the subsequent off-seasonal surge of RSV infections.Results We found a significant reduction in hospitalizations for RSV bronchiolitis during the usual winter epidemic period due to the COVID-19 pandemic. Children hospitalized with RSV infection in 2021, during the COVID-19 pandemic, were older than children hospitalized in the prepandemic period (2015–2020; 4.0 [1.6–9.2] vs. 3 [1.5–6.5] months; p < 0.01). We also found shorter duration of oxygen days during the COVID-19 period compared with previous respiratory seasons (3 [2–5] vs. 4 [2–6] days; p = 0.02).Conclusion The COVID-19 pandemic modified the RSV seasonality with a significant reduction in RSV hospitalizations during the expected 2020–2021 season and a reappearance of RSV 7 months later than expected. We also found changes in the median age of children with RSV bronchiolitis during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic compared with the prepandemic RSV seasons and shorter duration of oxygen days suggesting a modest reduction in disease severity. We hypothesize that this observation reflects the lack of RSV circulation in the previous months (April 2020-March 2021), with a larger pool of vulnerable infants that had not been previously infected.Key Points
Keywords: bronchiolitis; RSV; COVID-19; epidemiology